Treatment for Sexual Assault Survivors at University Counseling Centers. Issue 4 (1st October 2016) - Artime, Tiffany M.; Buchholz, Katherine R.
ABSTRACT: University Counseling Centers (UCCs) provide important services for sexual assault survivors, yet little research has been conducted on interventions used by clinicians in this unique setting. As a preliminary investigation, UCC professionals were asked about services provided to survivors of sexual assault and staff perceptions of the effectiveness of these interventions. Supportive counseling was perceived to be the most effective relative to other interventions, and many participants indicated that they did not use or were not sure if other evidence-based interventions were effective with student victims. Several recommendations for future research on sexual assault services in UCCs are suggested.